An All‐Optical, Non‐volatile, Bidirectional, Phase‐Change Meta‐Switch. (29th April 2013) - Gholipour, Behrad; Zhang, Jianfa; MacDonald, Kevin F.; Hewak, Daniel W.; Zheludev, Nikolay I.
<x xml:space="preserve">Abstract</x> Non‐volatile, bidirectional, all‐optical switching in a phase‐change metamaterial delivers high‐contrast transmission and reflection modulation at near‐ to mid‐infrared wavelengths in device structures down to ≈1/27 of a wavelength thick. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>